The Development of an Information System for Sustaining Energy Consumption in Smart Homes - Dzemydienė, Dalė; Žulkas, Evaldas (Information & Media, 2018)
Information systems play an important role in smart home management. They collect monitoring data for devices connected to a wireless network (e.g., sensors, lights, thermometers). Such systems are classified as complex modern electronic services management systems that can provide environmental management services in a smart home. However, in order for smart devices to be able to use energy efficiently, additional software modules are needed to make these devices more efficiently used. The purpose of our research work is to develop the functions of the information system, enabling the estimation of electrical energy consumption in the smart housing system and the use of forecasting data for controlling electricity costs.